Social skills and the individual wage growth of less educated workers - Philippe Aghion; Antonin Bergeaud; Richard W. Blundell; Rachel Griffith (Institute for Fiscal Studies (IFS), 2023)
We use matched employee-employer data from the UK to highlight the importance of social skills, including the ability to work well in a team and communicate effectively with co-workers, as a driver for individual wage growth for workers with few formal educational qualifications. We show that lower educated workers in occupations where social skills are more important experience steeper wage growth with tenure, and also higher early exit rates, than equivalent workers in occupations where social skills are less important. Moreover, the return to tenure in occupations where social skills are important is stronger in firms with a larger share of higher educated workers. We rationalize our findings using a model of wage bargaining with complementarity between the skills and abilities of less educated workers and the firm's other assets.
Keywords: J31; J24; L25; 330; team work; social skills; individual wage growth; firm pay premium